EMIMTFSI-Induced plasticization and crystallinity suppression in PEO/ ENR-25 polymer electrolytes: A DFT-assisted study of structural and electrochemical performance - Whba, Rawdah; Guler, Mihrihan; Gultek, Ahmet; Sahinbay, Sevda; Serin, Sumeyya; Canbay, Canan Aksu; Altin, Serdar (Pergamon-Elsevier Science Ltd, 2026)
This work addressed plasticized polymer electrolytes consisting of a fixed blend of poly(ethylene oxide) and 25% epoxidized natural rubber (ENR-25), doped with lithium bis(trifluoromethanesulfonyl)imide and varying contents of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide have been prepared and investigated to understand the conduction mechanism as a function of ionic liquid (IL) content. The inclusion of IL achieved the maximum ionic conductivity (6) of 1.59 & times; 10-5 S cm-1 at room temperature, the lithium-ion transference number (tLi+) of 0.57, and the electrochemical stability window (ESW) up to 4.9 V vs. Li/Li+. These effects are correlated with a considerable reduction in the glass transition temperature (Tg), which reflects the plasticizing effect of the IL and the enhanced segmental mobility of the polymers. Fourier transform infrared (FTIR) spectroscopy and density functional theory (DFT) calculations at the omega B97X-D/def2-TZVP level revealed the preferential coordination of Li+ ions to the ether groups of the PEO rather than ENR-25 epoxide sites. Frontier molecular orbital (FMO) and conceptual DFT (CDFT) further showed a reduction in the HOMO-LUMO gap (Delta E) and the chemical hardness (eta), which are indicators of the enhanced electronic softness. Overall, the results clearly establish that IL-induced Tg depression and changes in Li+ coordination chemistry have a direct influence on 6, Li+ mobility, and electrochemical stability.
Keywords: Polymer electrolyte; Poly (ethylene oxide) (PEO); ENR-25; Ionic liquid; Plasticization; Ion conduction; DFT calculation